1998
DOI: 10.1104/pp.116.1.231
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Salicylic Acid and 4-Hydroxybenzoic Acid in Phloem Fluids of Cucumber during Systemic Acquired Resistance Is Preceded by a Transient Increase in Phenylalanine Ammonia-Lyase Activity in Petioles and Stems1

Abstract: Cucumber (Cucumis sativa) leaves infiltrated with Pseudomonas syringae pv. syringae cells produced a mobile signal for systemic acquired resistance between 3 and 6 h after inoculation. The production of a mobile signal by inoculated leaves was followed by a transient increase in phenylalanine ammonia-lyase (PAL) activity in the petioles of inoculated leaves and in stems above inoculated leaves; with peaks in activity at 9 and 12 h, respectively, after inoculation. In contrast, PAL activity in inoculated leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 46 publications
(37 reference statements)
10
79
1
Order By: Relevance
“…Similar results were previously obtained by Vaughn and Duke (1984). Smith-Becker et al (1998) reported that the activities of polyphenol oxidase, peroxidase and PAL were increased in plants treated with various abiotic and biotic inducers. However, Cvikrova et al (1999) concluded that the inhibition of phenylpropanoid metabolism stimulated cell division during the growth cycle of alfalfa suspension cultures.…”
Section: Resultssupporting
confidence: 80%
“…Similar results were previously obtained by Vaughn and Duke (1984). Smith-Becker et al (1998) reported that the activities of polyphenol oxidase, peroxidase and PAL were increased in plants treated with various abiotic and biotic inducers. However, Cvikrova et al (1999) concluded that the inhibition of phenylpropanoid metabolism stimulated cell division during the growth cycle of alfalfa suspension cultures.…”
Section: Resultssupporting
confidence: 80%
“…Similar results were obtained by graftings between nontransformed tobacco plants and transgenics exhibiting epigenetic cosuppression of the PAL gene encoding phenylalanine ammonia-lyase, causing a strongly reduced biosynthesis of SA (Pallas et al, 1996). Indeed, Smith-Becker et al (1998) demonstrated that upon primary infection of a single cucumber leaf, the accumulation of SA in phloem fluids was preceded by a transient increase in PAL activity in the stems and petioles. These results suggested that SA is synthesized de novo in stems and petioles in response to an early mobile signal from the inoculated leaf.…”
Section: Signal Compounds Involved In Primarysupporting
confidence: 70%
“…Similarly, a rapid and transient induction of PAL activity was also observed in the necrotic reaction of cucumber plants against P. syringae pv. syringae infiltration (Smith-Becker et al, 1998), although in this 660 interaction, PAL activity correlated with an increment of phenolic 4-hydroxybenzoic acid. In two compatible interactions, cucumber/prunus necrotic ring spot virus and melon/melon necrotic spot virus, an induction of PAL gene expression was also observed, but occurred at later time points (Bellés et al, 2008).…”
Section: (Trans-cna) (2) Trans-n-feruloylnoradrenaline (Trans-fna) (mentioning
confidence: 98%